Kinetic Thinking Styles: A tool for developing entrepreneurial thinking - Pistrui, Joseph; DIMOV, Dimo (My University, 2023)
In this paper, we introduce a set of instructional tools (Kinetic Thinking Styles framework) focused on developing entrepreneurial thinking by stimulating metacognitive awareness and fostering learning environments that are conducive to metacognition. We provide an account of the development of the framework, including its conceptual underpinnings, synthesis of a map of thinking styles that can help us understand how thinking operates in entrepreneurial situations, and the design process for the creation of an assessment tool (mirror) of one’s thinking style. We illustrate how this suite of tools can be used in educational settings, including an example of a newly designed thinking tune-up course and a framework for understanding challenges for diverse learner populations.
Keywords: Design science; Entrepreneurship education; Entrepreneurial thinking; Metacognition; Personal developmen; 58 Pedagogía; ODS 4 - Educación de calidad